Toxic Spongiform Leukoencephalopathy After Intravenous Heroin Abuse: Unusual But Important Differential Diagnosis of Acute Impairment of Consciousness - Diefenbach, Camilla; Lorenz, Christine; Weidauer, Stefan (Fortschritte der Neurologie · Psychiatrie, 2022)
Abuse of heroin vapour inhalation known as “chasing the dragon” is associated with toxic spongiform leukoencephalopathy. However, similar clinical and imaging findings may occur also after intravenous heroin abuse. We report on a 32-year-old male suffering from extensive toxic spongiform leukoencephalopathy after intravenous heroin abuse resulting in acute impairment of consciousness and a global state of confusion. MRI disclosed broad and nearly symmetrical diffusion restriction of the supratentorial white matter indicating cytotoxic oedema. In an emergency setting, differential diagnosis of acute impairment of consciousness and broad symmetrical white matter lesions in neuroimaging should also include toxic leukoencephalopathy due to intravenous heroin application.
Keywords: acute impairment of consciousness; chasing the dragon; toxic spongiform leukoencephalopathy; intravenous heroin abuse; MRI